LINGUISTIC EXPRESSION OF NATIONAL MENTALITY IN LITERARY TEXTS (SCIENCE TIME JOURNAL, 2026)
This article analyzes the linguistic means of expressing national mentality in literary texts. The study examines the reflection of national consciousness, cultural values, traditions, and collective worldview through language units in artistic discourse. Particular attention is paid to the linguopoetic functions of lexical, phraseological, and symbolic devices representing national mentality in literary texts. The findings demonstrate that language units perform important semantic and aesthetic functions in shaping the national-cultural content of artistic discourse.